Halal food certification: case of Malaysian SME entrepreneurs - Abdul, Mohani; Ismail, Hashanah; Mustapha, Mazlina (David Publishing Company, 2013)
This paper reports on 108 Malaysian SME entrepreneurs’ perceptions towards Halal Food Certification (HFC) in Malaysia along four dimensions of market share and market competitiveness, government support and monitoring, information dissemination and rigor of certification process using a structured questionnaires distributed during MIHAS 2011. Based on their responses, the study finds that HFC is important to promote customers’ confidence, trust, and satisfaction but they were of the opinion that the contents of information were insufficient. Respondents ranked certification process as tedious and stringent hence needs to be improved. They were dissatisfied with the information dissemination on halal hub. Hence the government needs to improve its support and monitoring system. The study also indicates that respondents who have attended entrepreneurship courses, have ventured into international markets, have obtained Halal Certification for their food products and attained at least a bachelor degree level of education have significant different responses towards the HFCs.